THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND INFORMATION TECHNOLOGY ON ORGANIZATIONAL LEARNING AND ORGANIZATIONAL CHANGE, AND ITS IMPACT ON EMPLOYEE JOB SATISFACTION (STUDY ON PT PUPUK KALTIM EMPLOYEES) - Pasaman, Achmad Bakir; Nimran, Umar; Raharjo, Kusdi; Utami, Hamidah Nayati (Accounting Department, 2018)
The purpose of this study is to examine the effect of transformational leadership and information technology on organizational learning and organizational change and its impact on employee job satisfaction at PT. Pupuk Kaltim. The study is conducted by analyzing the effect between variables consisting of 2 (two) exogenous variables: Transformational Leadership (X1) and Information Technology (X2), and 3 (three) endogenous variables: Organizational Learning (Y1), Organizational Change (Y2) and Employee Job Satisfaction (Y3). This study is designed to answer the problem statements that have been formulated. The study method is an explanatory research. The population is employees of PT. Pupuk Kaltim, where the size of its sample is of 207 respondents. The data is collected using proportional stratified random sampling method to find the effect between exogenous variables and endogenous variables. The findings of the study are from the 9 (nine) hypotheses tested, 8 (eight) hypotheses have significantly affected on the variables studied. The only one which has no significant effect is Transformational Leadership on Employee Job Satisfaction, where it needs to be mediated by organizational learning and organizational change.